Prospects of royal jelly as a potential natural feed additive in poultry diets. Issue 3 (September 2018) - SAEED, M.; KALHORO, S.A.; NAVEED, M.; HASSAN, F.U.; UMAR, M.; RASHID, M.; MEMON, S.A.; SOOMRO, F.; ARAIN, M.A.; CHAO, S.
Abstract : Royal Jelly (RJ) is product from bees that is used to feed larvae in the hive as well as a main nutritional source for the queen honey bee. It has various important biological activities including as an antioxidant, immunomodulatory, anti-inflammatory, antimicrobial, cholesterol-lowering, and growth promoter activities and has the ability for inhibition of certain enzymatic degradation. It can be used for the improvement of growth performance, gut health and quality and safety of animal products in poultry due to its antioxidant and immune modulating properties. The antioxidant activity of RJ is mainly due to the presence of polyphenolic compounds. It is an excellent source of B and C vitamins and folic acid. The mineral profile of RJ is useful as it contains major macro and micro minerals. Studies conducted on supplementation with RJ in poultry diets have shown a significant increase in body weight, egg production, and immune levels and is especially useful in organic production. Supplementation of RJ at the level of 10 and 15 mg/kg in layer diets positively influenced egg weight (by 5.0% and 4.8% respectively), egg production (10.5% and 11.0% respectively), weight gain of hens (7.0% and 6.5% respectively) and yolk pigmentation (9.5% and 9.7% respectively). Total leukocyte and erythrocyte counts in the diet containing 200 mg/kg RJ were significantly higher than the diet contained 100 mg/kg or the unsupplemented control group. However, the heterophil/lymphocyte ratio and heterophil percent were reduced in RJ-fed groups. Supplementing poultry diets with RJ offers an opportunity to maximise profit from safe and high quality poultry production.